Extending the Vase Life of Cut Gerbera (Gerbera jamesonii Bolus ex. Hook) cv. Savannah by Using Locally Available Floral Preservat ives under Ambient Storage - Murthy, K. C. Bhanu; Prashanth, P.; Chandrasekhar, R. (International Journal of Bio-resource and Stress Management, 2015)
A laboratory trial was carried out to investigate the effectiveness of different locally available floral preservatives on extension of vase life of cut gerbera cv. Savannah under ambient storage condition. All the cut gerberas were precooled at 5 °C for 6 hours and followed by pulsing with sucrose at 20%+sodium hypochlorite at 50 ppm for 12 hours and then kept in locally available preservative floral solutions i.e.sugar, commercial vinegar, lime (Citrus aurantifolia) juice, commercial bleach (calcium hypochlorite-CaOCl2) and neem (Azadirachta indica) extract at different concentrations in combination with 4% sucrose. Using the solution of neem extract at 1% coupled with 4% sucrose significantly maintained water relations and reduced scape bending curvature as compared to all other treatments. Total soluble solids in flower stalk and anthocyanin content in ligules of cut gerberas kept in neem extract at 1%+4% sucrose solution were also highest i.e. (10.08 °Brix) and (5.83 mg Congo Red g-1 f wt) respectively. The cut gerberas held in solution of neem extract at 1%+sucrose at 4% recorded lowest optical density (0.041) which was attributed with lowest microbial count (4.26×105 cfu ml-1) and resulted in highest vase life (11.76 days) compared to control (4.53 days) which recorded highest microbial count (8.99×106 cfu ml-1).